Influence of the welding process on the martenistic high strength steel - Hanus, Petr; Schmidová, Eva; Tomanovič, Josef (Univerzita Pardubice, 2014)
The subject of the study are martensitic 22Mn5B steels, which are used in the automotive industry. The main purpose of the performed analyses is a study of strength differences in heat affected zones of the spot welding. For the needs of the strength decrease assessment, the critical layer of the heat affected area was experimentally simulated. The aim of the work is to determine the most suitable methodology for evaluating the local changes of the elastic-plastic material response. The aim of this work is to determine the optimal methods for the determination of the yield strength and to find a firming trend in these zones.